Crossmodal change blindness between vision and touch. - Auvray, M; Gallace, A; Tan, H; Spence, C (2007)
Change blindness is the name given to people's inability to detect changes introduced between two consecutively-presented scenes when they are separated by a distractor that masks the transients that are typically associated with change. Change blindness has been reported within vision, audition, and touch, but has never before been investigated when successive patterns are presented to different sensory modalities. In the study reported here, we investigated change detection performance when the two to-be-compared stimulus patterns were presented in the same sensory modality (i.e., both visual or both tactile) and when one stimulus pattern was tactile while the other was presented visually or vice versa. The two to-be-compared patterns were presented consecutively, separated by an empty interval, or else separated by a masked interval. In the latter case, the masked interval could either be tactile or visual. The first experiment investigated visual-tactile and tactile-visual change detection performance. The results showed that in the absence of masking, participants detected changes in position accurately, despite the fact that the two to-be-compared displays were presented in different sensory modalities. Furthermore, when a mask was presented between the two to-be-compared displays, crossmodal change blindness was elicited no matter whether the mask was visual or tactile. The results of two further experiments showed that performance was better overall in the unimodal (visual or tactile) conditions than in the crossmodal conditions. These results suggest that certain of the processes underlying change blindness are multisensory in nature. We discuss these findings in relation to recent claims regarding the crossmodal nature of spatial attention.